ABOUT HOLINESS AND PIETY IN MODERN ARABIC LITERATURE - N. A. Uspenskaya (Концепт: философия, религия, культура, 2019)
These chapters are taken from monographies of N. Uspenskaya “East – West – Russia: the protheses of culture interaction”. In these chapters the author touches the themes of holiness and piety, faith and national conciseness, spirituality and intercourse with God in pray, relations between eastern traditionalists and the supporters of the west way of development. These categories are shown through the heroes of the works of contemporary Arabic writers such as “The saint’s lamp” by Yahya Haqqy, “The apogees of love” by Ihsan Abdel Kuddus, “Three orange trees” by Yahya Tahir Abdalla, “Days” by Taha Husein compared to such works as “White Guards” by Mihail Bulgacov, “The nights of Cabiria” the flm of Federico Felliny, “ The book of meditation and quiet contemplations” by Ivan Ilin and some works by Chekhov. The task of the author is to show by these examples the place of Arabic writers in World literature, their relation to famous works and their authors, to show the common features and common points of view. The author of the monographies touches the problem of intercourse between religion and science, which was shown by Yahya Haqqy in his “Saint’s lamp”, as well as the attitude of western and eastern intellectuals to it. In these chapters the author compares the values of such religions as Islam and Christianity and shows its realization in the heroes of works of considered authors. Here also shown the history of development of the problem of East and West and its reﬂection in mentioned above works.